Effects of graphene content on the microstructure and mechanical properties of alumina-based composites - Zhu, Jun; Jia, Bi; Di, Yongjiang; Liu, Biao; Wan, Xin; Wang, Wenrong; Tang, Rui; Liao, Shu; Chen, Xingyu (Frontiers in Materials, 2022)
In this work, alumina-graphene (Al2O3-G) composites with graphene contents ranging from 0.5% to 3% were prepared by stepwise feeding ball milling and hot pressing. The influences of graphene content on the microstructure and mechanical properties of Al2O3-G composites were investigated. Results showed that the densification, grain sizes, flexural strength, fracture toughness and Vickers hardness of materials increased firstly and then decreased with increasing graphene contents. When the graphene content was 1%, the value of each performance parameter reached the maximum. The average grain size of material decreased from 991 nm to 551 nm as the graphene content increased from 0 to 1%, but it increased to 863 nm when the graphene content was 3%. The flexural strength, fracture toughness and Vickers hardness of composites with graphene content of 1% increased to 763.5 MPa, 7.4 MPa·m1/2 and 21.28 GPa. Compared with the Al2O3, the fracture strength and toughness of the composites increased by up to 54.63% and 65.54%. Analysis suggested that the strength of Al2O3-G composites was mainly related to the grain size and preexisting microflaws.